“Trouble Child”: Joni Mitchell’s Adoption Story and Attitudes about Unwed Motherhood in 1960s Ontario - Penney, Annabelle (Ontario History, 2026)
In the summer of 1964, first-year Alberta College of Art and Design student Roberta Joan Anderson (soon to be Joni Mitchell) dropped out of college and fled to Canada’s most cosmopolitan city: Toronto. Twenty years old, pregnant, unwed, and utterly terrified, Mitchell was still a perennial pragmatist. She envisioned Toronto as an environment more hospitable to the life she wanted to lead—a life that deviated from normative Canadian cultural values and saw her becoming both a single mother and a female singer-songwriter. This article examines an understudied period in the life of musical legend Joni Mitchell. It expands on existing studies of Mitchell’s early career and on the experiences of unwed mothers living in 1960s Toronto. In it, I illuminate the context-specific considerations that led to Mitchell’s decision to leave Alberta and interrogate what normative expectations of motherhood looked like in the Canadian Prairies versus postwar Ontario. After being turned away from the Salvation Army’s Bethany Home for Unwed Mothers, Mitchell gave birth alone to her daughter on February 19, 1965. She left the hospital the next day, her daughter placed into foster care. Mitchell is one of thousands of Canadian women whose lives were irrevocably impacted by Canada’s postwar adoption mandate programs. As a public figure who has gone on record about the mistreatment she suffered while pregnant and unwed, Mitchell grants us access to a domain of Canadian history where voices are notoriously difficult to find, given the shame and stigma surrounding unwed motherhood. Mitchell becomes a totem through which to discuss the enduring legacy of Canada’s postwar adoption mandate for single mothers and the climate of hostility that unwed Canadian mothers in 1960s Ontario were forced to navigate.